Exploring the relationships between the enablers and results criteria of the EFQM model 2013 in the context of the Greek public administrative services - Dimitra Mitsiou; Kostas Zafiropoulos (Administrative Sciences, 2024)
This study presents a first attempt to apply and validate the European Foundation for Quality Management (EFQM) Model 2013 as a framework in the context of public administrative services in Greece, and to explore the relationships between the model's enablers and results criteria. The methodological approach adopted was quantitative research with a structured questionnaire, while partial least squares structural equation modeling (PLS-SEM) was applied to validate the model and test the cause-effect relationships between the enablers and results on a national sample of 155 managers. The results confirmed the reliability and validity of the EFQM Model 2013 in the context of this study and revealed significant relationships between the model's enablers and results. In addition, the empirical findings of this study may improve our understanding of the underlying relationships between the EFQM model criteria, but should not be generalized, as this study only concerned Greek public administrative services. Finally, this study may provide valuable insights to managers and governing bodies responsible for policy-making about the significance and magnitude of the relationships between the enablers and results criteria so that they can develop strategies to improve the operational and strategic performance of the Greek public administrative services.
Keywords: 350; EFQM Model 2013; enablers; results; causal relationships; public administrative services; Greece; structural equation modeling; partial least squares; PLS-SEM; SmartPLS